2022
DOI: 10.1007/s00426-022-01768-7
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing motor imagery practice using synchronous action observation

Abstract: In this paper, we discuss a variety of ways in which practising motor actions by means of motor imagery (MI) can be enhanced via synchronous action observation (AO), that is, by AO + MI. We review the available research on the (mostly facilitatory) behavioural effects of AO + MI practice in the early stages of skill acquisition, discuss possible theoretical explanations, and consider several issues related to the choice and presentation schedules of suitable models. We then discuss considerations related to AO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 173 publications
0
16
0
Order By: Relevance
“…Research from Rüther et al ( 2014) also found the action observation network, which comprises sensorimotor brain regions, was engaged when participants observed a novel object construction task from a visual picture matching cue or a partner who sat opposite. Importantly, while AO has been found to evoke activity in the areas of the brain that partially overlap with those responsible for movement execution (Caspers et al, 2010), a crucial limitation of AO is that it provides a visual representation of an action, without necessarily involving a sense of agency in the observer, nor promoting a focus on one's own body schema and the related kinesthetic sensations of the observed action (Eaves et al, 2022).…”
Section: The Effects Of Practice Condition On Motor Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Research from Rüther et al ( 2014) also found the action observation network, which comprises sensorimotor brain regions, was engaged when participants observed a novel object construction task from a visual picture matching cue or a partner who sat opposite. Importantly, while AO has been found to evoke activity in the areas of the brain that partially overlap with those responsible for movement execution (Caspers et al, 2010), a crucial limitation of AO is that it provides a visual representation of an action, without necessarily involving a sense of agency in the observer, nor promoting a focus on one's own body schema and the related kinesthetic sensations of the observed action (Eaves et al, 2022).…”
Section: The Effects Of Practice Condition On Motor Learningmentioning
confidence: 99%
“…AO+MI may therefore promote functional connectivity and plasticity within the brain in a unique way, facilitating motor execution as learning progresses (see O'Shea & Moran, 2017). Moreover, it is possible that the benefits found for combined AO+MI training resulted from a process whereby both an 29 AO-triggered representation and an MI-generated representation was maintained either in parallel or were merged to consolidate motor processes and facilitate the early phase of motor learning (Eaves et al, 2022).…”
Section: The Effects Of Practice Condition On Motor Learningmentioning
confidence: 99%
“…There has been considerable research interest directed to determining the combined effects of AO+MI for practice, with the assumption that these covert states activate different processes that together can augment performance and learning experiences for individuals (for reviews see Eaves et al ., 2022; Scott et al ., 2022). Our data are generally in alignment with conclusions from this work, showing that there are behavioural as well as neurophysiological control related differences between AO and MI.…”
Section: Discussionmentioning
confidence: 99%
“…(2) executive functions during perceptual-cognitive scaffolding (Glover & Baran, 2017), (3) simulation in perceptualcognitive scaffolding (Jeannerod, 2001); (4) inverse and/ or forward models during imagery and imagery practice (Bach et al, 2022;Rieger et al in this issue); to (5) the manipulation of aspects of the movement representation such as its (multi)sensory quality of imagery (for a review, see Krüger et al, 2022), and (6) the exploration of superadditive effects of action observation as a truly sensory format to the imagery process(see Eaves et al, 2022).…”
Section: Understanding Learning Via Imagery -Quo Vadis?mentioning
confidence: 99%